Fever, Myositis, and Paralysis: Is This Inflammatory Myopathy or Neuroinvasive Disease? - Aneeta R. Kiran; Richard A. Lau; Kim M. Wu; Andrew L. Wong; Philip J. Clements; Emil R. Heinze (Case Reports in Rheumatology)
West Nile virus (WNV) is a mosquito-borne RNA Flavivirus which emerged in North America in 1999. Most patients present with a febrile illness but a few develop WNV neuroinvasive disease. Myopathy is an uncommon manifestation. We describe a case of a 42-year-old male from Los Angeles who presented with 8 days of fever and muscle pain. Initial physical exam was normal except for 4/5 muscle strength testing in his extremity proximal muscles. Laboratory revealed a creatine kinase of 45,000 and a urinalysis with large blood but no red blood cells, suggesting rhabdomyolysis. The patient’s condition declined despite aggressive supportive care and hydration, and on hospital day #6 he developed severe altered mental status and progressed to complete right arm paralysis and 2/5 muscle strength in bilateral legs. EMG/NCS showed sensorimotor axonal polyneuropathy and the cerebrospinal fluid was positive for IgM and IgG WNV antibodies. The patient was diagnosed with WNV neuroinvasive disease, poliomyelitis (and encephalitis) type with myopathy/muscle involvement. He was treated supportively and his muscle and neurologic disease gradually improved. At 12-month follow-up his muscle enzymes had normalized and his weakness had improved to 5/5 strength in bilateral legs and 3/5 strength in the right arm.